Análise da polivalência em células de manufatura e sua relação com a qualidade e a produtividade: estudo de caso em uma empresa do setor calçadista - Alencar, Francisca Alixandrina Leonardo (2017)
To promote a multi-skilled and flexible workforce, companies with continuous flows into manufacturing cells apply polyvalence, a means of leveraging workers' knowledge and skills. In this context, the objective of this dissertation is to identify the polyvalence profile in manufacturing cells of a unit of the footwear sector and its relationship with indicators of quality and productivity. To achieve this objective, a qualitative-quantitative approach was used as a descriptive and exploratory research, first defining a conceptual framework and selecting parameters in the literature for evaluation of polyvalence. Based on these parameters, the polyvalence profile of the manufacturing cells is constructed and the Spearman coefficient correlates the polyvalence profile to the quality indicators by First-timethrough (FTT) and productivity per manpower. According to the results, it was possible to verify the indicators with the highest and lowest scores in the polyvalence profile of the groups of cells studied. There was also a very low correlation between polyvalence and quality and between polyvalency and productivity, concluding that in the cells studied there is no link between polyvalence profile and productivity, as well as between polyvalence profile and quality. However, other aspects may be influencing this result, such as the lack of programming for the balancing of production lines in low demand and the rotation of the operators between the stations and between the cells.